2006
DOI: 10.1111/j.1574-0862.2006.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Prices of American Pinot Noir wines: climate, craftsmanship, critics

Abstract: Pinot Noir, a variety originating from Burgundy in France, is the most expensive category of table wine produced in North America. This article is aimed at analyzing its price determinants and focuses on climate, critical scores, and variables related to the winemaker. The main findings are as follows: (1) Pinot Noir prices are mainly determined by temperature and precipitation. General temperature increases are not beneficial. In fact, the optimal climate is similar to that in Burgundy. (2) The second most im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 12 publications
6
104
0
5
Order By: Relevance
“…In a similar fashion, Haeger and Storchmann (2006) and Jones and Storchmann (2001) report cross-sectional real rate of returns for selected châteaux of Bordeaux wines and California pinot noirs, respectively, that are significantly below those for common stock (see Table 5). …”
Section: Wine and Financementioning
confidence: 99%
See 2 more Smart Citations
“…In a similar fashion, Haeger and Storchmann (2006) and Jones and Storchmann (2001) report cross-sectional real rate of returns for selected châteaux of Bordeaux wines and California pinot noirs, respectively, that are significantly below those for common stock (see Table 5). …”
Section: Wine and Financementioning
confidence: 99%
“…This result finds further support from the fact that weather data are excellent predictors of the experts' ratings. Haeger and Storchmann (2006) pursued a similar sequential approach and found that Wine Spectator points only marginally improve weather-based models of U.S. pinot noir wine prices. Jones and Storchmann (2001) differentiated this approach by château and reported that prices of smaller châteaux, those that make 15 Other outstanding Parker-rated Bordeaux vintages are (number of 100-point wines in parenthesis): 2000 (7), 1961 (4), 1945 (3), 1989 (3) and 1990 (3).…”
Section: A Expert Ratings and Price Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Lancaster's theory states that consumers do not obtain utility directly from the goods that they consume but from the combination of characteristics that the goods possess, whilst Rosen's (1974) approach, allows to obtain the implicit price for each of these characteristics. The hedonic price approach has been employed in a wide set of economic areas, such as housing and environmental services, whilst applications in agro-food products, have focused mainly on wine (with recent applications by Durham et al, 2004;Haeger and Storchmann, 2006;Costanigro et al, 2007), and meat (Loureiro and McCluskey, 2000;Gracia and Pérez-yPérez, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Different varieties, regions, vineyards, vintages, wineries and wines command significantly different prices for their winegrapes in Australia (Allen 2003). This price differential has been linked to wine and winegrape quality in some studies (Golan & Shalit 1993, Oczkowski 1994, Unwin 1999, Haeger & Storchmann 2006 Harvest maximum temperature (mean, December-March) (°C)…”
Section: Selecting a Winegrape Quality Indicatormentioning
confidence: 99%